Investigation of biocorrosion on mild steel in cooling tower water and its inhibition by C. sativum - Sharmil Suganya R; Stanelybritto Maria Arul Francis; T Venugopal (AIMS Molecular Science)
The primary goal of this investigation was to evaluate the effect of Coriandrum sativum extract on mitigating corrosion caused by Staphylococcus aureus, Klebsiella pneumonia, and Bacillus subtilis on metal samples. Analytical methods including SEM, FTIR, and XRD examination were used on the metal surface to determine the mechanism underlying corrosion inhibition. Impedance studies and Nyquist plots were used to support the role of green inhibitors in biocorrosion control. Based on analytical examinations, the corrosion patterns in some pitted zones showed a substantial link between microbial metabolites and the chemical composition of the metal surface. The presence of microbial metabolites caused the metallic surface to become more porous and permeable, changing the surface's structural makeup. In all three bacteria, 30 ppm of plant extract was found to be the maximum concentration that inhibited microbial corrosion. The coupons submerged in the control solution lost weight, indicating that the addition of the inhibitor caused a brief increase in corrosion rates before they declined.